Cholestatic Jaundice With the Use of Methylstenbolone and Dymethazine, Designer Steroids Found in Super DMZ Rx 2.0 "Nutritional Supplement": A Case Report. (22nd April 2014) - Agbenyefia, Priscilla; Arnold, Christina A.; Kirkpatrick, Robert
"Nutritional supplements" that promise an increase in muscle mass and strength are becoming a go to item as enhancing one's physical appearance becomes a more important part of our society. This is alarming because many of these nutritional supplements rely on androgen precursors to deliver their promises, without adequately informing consumers of the potential side effects of such agents. These products may conceal the presence of potent androgens to avoid regulatory sanctions and become more appealing to consumers. Recent reports have shown that some products marketed as "nutritional supplements" have been found to contain androgenic anabolic steroids. Methylstenbolone and dymethazine are new androgenic anabolic steroids currently gaining popularity among body builders for their performance-enhancing properties and rapid effects on muscle mass. These agents are found together in Super DMZ Rx 2.0, a "dietary supplement" for bodybuilders. Here we report the first case of Super DMZ Rx 2.0–induced cholestatic jaundice in a 26-year-old previously healthy Caucasian male, who took the supplement according to the manufacturer's instructions for 30 days.